Abstract 067: Outcomes for large vessel occlusion patients with severe baseline disability with and without endovascular thrombectomy - Amine J. Awad; Michael J. Young; Alexander Andreev; Adam A. Dmytriw; Justin E. Vranic; James D. Rabinov; Christopher J. Stapleton; Alvin S. Das; Anna K. Bonkhoff; Lara Carvalho de Oliveira; Markus D. Schirmer; Thabele M. Leslie‐Mazwi; et al. (Stroke: Vascular and Interventional Neurology)
Introduction Patients with baseline disability account for one‐third of stroke presentations. However, there remains controversy in treatment selection for endovascular thrombectomy (EVT). We compared long‐term outcomes and likelihood of transitioning to comfort care for large vessel occlusion (LVO) patients with severe pre‐stroke disability treated with EVT versus medical management at a single center from 2017‐2020. Methods Individuals who presented with LVO were identified retrospectively from a prospectively maintained database. Severe baseline disability was defined as modified Rankin Scale (mRS) 3‐5. Delta mRS was defined as the difference between baseline and 90‐day mRS. Logistic and ordinal regressions were performed to evaluate the relationships between EVT and outcomes. A mixed‐methods analysis was performed to assess rates and reasons for transitions to comfort care. Results A total of 175/1008 (17%) were identified with severe baseline disability. The median age was 82 (IQR 70‐89), and 59% were female. Thirty‐two (18%) with severe baseline disability were treated with EVT. EVT was independently associated with improved delta mRS (B=‐1.048; 95%CI=‐1.777,‐0.318; p=0.005) accounting for age and NIHSS. However, EVT did not reduce the odds of transitioning to comfort care (aOR=0.794; 95%CI=0.347,1.818; p=0.585) accounting for age and NIHSS. Seventy‐six (43%) with severe baseline disability were transitioned to comfort care. Of the 99 not transitioned to comfort care, 18 were treated with EVT, and EVT was independently associated with improved delta mRS (B=‐2.794; 95%CI=‐4.002,‐1.586; p<0.0001) accounting for age and NIHSS. The median time from presentation to comfort care was 2 days (IQR 1‐7) in the non‐EVT group, compared to 7 (IQR 4‐11) in the EVT group (H(1)=5.46, p=0.019). The primary reasons for comfort care were poor perceived prognosis and medical complications. Conclusion Among patients with severe baseline disability, EVT is associated with less post‐stroke accumulated disability without limiting transitions to comfort care. EVT may be compatible with goal‐concordant care and should not be routinely withheld on the basis of baseline disability alone.